2010
DOI: 10.13031/2013.29556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Grape Quality Parameters by a Simple Vis/NIR System

Abstract: Visible/near-infrared (Vis/NIR) spectroscopy is a rapid and nondestructive technique requiring minimal sample processing before analysis, and coupled with chemometrics methods it appears to be one of the most convenient and straightforward analytical tools for studying fruit quality and ripeness. Chemometrics is applied to solve both descriptive and predictive problems in the chemical, pharmaceutical, and food sectors. With this aim, an optical, portable, experimental system (Vis/NIR spectrophotometer) for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 9 publications
2
48
1
Order By: Relevance
“…Larrain et al [28] also obtained R 2 ¼ 0.87 in validation for SSC using a portable NIR device (640-1300 nm) on Chardonnay grapes under field conditions. Regarding TA, Guidetti et al [29], using a portable vis/NIR system (450-980 nm), showed for fresh berries of red Nebbiolo grapes R 2 cv ¼0.66 and RMSECV¼ 1.48 g dm À 3 . Spectral indexes measured at the four wavelengths on the same samples was used to predict the ripening parameters using MLR analysis ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Larrain et al [28] also obtained R 2 ¼ 0.87 in validation for SSC using a portable NIR device (640-1300 nm) on Chardonnay grapes under field conditions. Regarding TA, Guidetti et al [29], using a portable vis/NIR system (450-980 nm), showed for fresh berries of red Nebbiolo grapes R 2 cv ¼0.66 and RMSECV¼ 1.48 g dm À 3 . Spectral indexes measured at the four wavelengths on the same samples was used to predict the ripening parameters using MLR analysis ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In PLS regression, an orthogonal on the basis of latent variables (LVs) is constructed one by one in such a way that they are oriented to along directions of maximal covariance between the spectral matrix and the variable matrix (Guidetti et al 2010). The LVs were determined using leave-one-sample-out crossvalidation (LOOCV) method combined with the smallest root-mean-square error of cross-validation (RMSECV).…”
Section: Partial Least Squaresmentioning
confidence: 99%
“…They observed that RF treatments, combined with forced hot air at 48°C for 10 min, followed by forced room air cooling through a 3 cm product layer, provided good bean quality. Guidetti et al (2010) investigated a portable optical experimental system (Vis/NIR spectrophotometer) for nondestructive and quick prediction of ripening parameters of fresh berries and homogenized grape samples (Vitis spp.) in the wavelength range of 450-980 nm.…”
Section: Transactions Of the Asabe (American Society Of Agricultural mentioning
confidence: 99%